PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK TERPADU DENGAN MODEL TEAM QUIZ DI SD - Marici Sartika, Ranta; Sri Lena, Mai (STKIP Subang, 2021)
This research aims to increase student learning outcomes using the Team Quiz model in class IV SD Negeri 12 Padang Kubu. This research is included in the type of CAR research using qualitative and quantitative approaches. The subjects of this research were teachers and 16 fourth grade students. This research was conducted in two cycles. As a result of this research proves the development that occurs in cycles I and II. The planning aspect of Cycle I obtained an average of 81.94 (B) developed in Cycle II 94.44 SB). In the implementation of the teacher education aspect in the first cycle, the average score was 88.63 (SB) then increased to 97.72 (SB) in the second cycle and 85.22 increased to 95.45 in the student implementation. While student learning outcomes obtained an average of 69.09 and 80.46 in the second cycle